Rh blood phenotyping (D, E, e, C, c) microarrays using multichannel surface plasmon resonance imaging - Chinnawut Pipatpanukul (2019)
© 2017 Elsevier B.V. The application of Surface Plasmon Resonance Imaging (SPRi) for the detection of transmembrane antigen of the Rhesus (Rh) blood group system is demonstrated. Clinically significant Rh blood group system antigens, including D, C, E, c, and e, can be simultaneously identified via solid phase immobilization assay, which offers significant time savings and assay simplification. Red blood cells (RBCs) flowed through the micro-channel, where a suitable condition for Rh blood group detection was an RBC dilution of 1:10 with a stop-flow condition. Stop flow showed an improvement in specific binding compared to continuous flow. Rh antigens required a longer incubation time to react with the immobilized antibody than A and B antigens due to the difference in antigen type and their location on the RBC. The interaction between the immobilized antibodies and their specific antigenic counterpart on the RBC showed a significant difference in RBC removal behavior using shear flow, measured from the decay of the SPR signal. The strength of the interaction between the immobilized antibody and RBC antigen was determined from the minimum wall shear stress required to start the decay process in the SPR signal. For a given range of immobilized antibody surface densities, the Rh antigen possesses a stronger interaction than A, B, and AB antigens. Identification of 82 samples of ABO and Rh blood groups using SPRi showed good agreement with the standard micro-column agglutination technique. A wider coverage of antigenic recognition for RBC when using the solid phase immobilization assay was demonstrated for the RBC with the antigenic site located on the transmembrane protein of the clinically significant Rh antigen. Given the level of accuracy and precision, the technique showed potential for the detection of the Rh minor blood group system.